Global Oncology Authorship and Readership Patterns - Maria T. Bourlon; Brenda Jiménez Franco; Francisco J. Castro-Alonso; Christianne Bourlon; Charbel F. Matar; Emilie Gunn; Ophira Ginsburg; Gilberto Lopes; Eva Segelov (JCO Global Oncology, 2022)
PURPOSEGlobal Oncology is the movement to improve equitable access to cancer control and care, recognizing challenges because of economic and social factors between high-, middle-, and low-income countries (HIC, MIC, and LIC, respectively). The JCO Global Oncology (JCO GO) is a major platform dedicated to publishing peer-reviewed research relevant to populations with limited resources. To assess the success of its goals of encouraging global interaction and increasing MIC and LIC engagement, we analyzed authorship and readership patterns.METHODSMetadata of logged views between January 1, 2018, and June 30, 2019, of articles published in 2018 by JCO GO were identified using Google Analytics. The country of origin of each author and those who accessed the journal were categorized according to the 2019 income group World Bank Classification (WBC).RESULTSOne hundred thirty-two articles were published in JCO GO in 2018. Corresponding authors came from 34 nations: 35% HIC, 47% MIC, and 18% LIC. The top publishing countries were the United States, India, Brazil, Mexico, and Nigeria. Article authors were solely from within one WBC group in 41% (23% HIC, 16% MIC, and 2% LIC). In those with mixed-WBC authorship origins, collaborations were 42% HIC + MIC, 11% HIC + LIC, and 6% HIC + MIC + LIC, but none with MIC + LIC. Regarding viewing, 87,860 views originated from 180 countries (82% of the WBC list): 35% HIC, 51% MIC, and 14% LIC. The most common accessing nations were the United States, India, the United Kingdom, Brazil, and Ethiopia.CONCLUSIONMore than half of JCO GO's authorship comes from mixed WBC groups, with viewership extending to most of the world's nations. Areas to address are low level of LIC corresponding authors, few papers from authors across all WBC groups, no publications from MIC + LIC collaborations, and a low percentage of readership by LIC. These data provide focus to target interventions aimed at reducing the academic segregation of LIC and improving interactions across all WBC countries.